Yoga Practice as a Potential Sarcopenia Prevention Strategy in Indonesian Older Adults: A Cross-Sectional Study - Meiliana A; Dewi NM; Latarissa IR; Barliana MI; Alfian SD; Yulianti T; Wijaya A (Open Access Journal of Sports Medicine)
Anna Meiliana,1,2 Nurrani Mustika Dewi,2,3 Irma Rahayu Latarissa,1 Melisa Intan Barliana,3,4 Sofa Dewi Alfian,1,4 Trilis Yulianti,2 Andi Wijaya2 1Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, Indonesia; 2Prodia Clinical Laboratory, Jakarta, Indonesia; 3Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, Indonesia; 4Center of Excellence for Pharmaceutical Care Innovation, Universitas Padjadjaran, Sumedang, IndonesiaCorrespondence: Anna Meiliana, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jl. Raya Bandung Sumedang KM. 21, Jatinangor, West Java, 45363, Indonesia, Email anna.meiliana@unpad.ac.idBackground: Sarcopenia is characterized by the progressive loss of skeletal muscle mass and poses a significant health challenge for older adults by increasing the risk of disability and decreasing quality of life. Yoga considers as a low-risk and beneficial exercise for older adults. This research aims to evaluate the potential of yoga practice as a preventive strategy against sarcopenia in Indonesian older adults.Methods: An observational cross-sectional research was conducted including 41 older adults aged 60– 87 years. The research focused on key biomarkers and functional assessments, including serum insulin-like growth factor 1 (IGF-1) levels, telomere length, gait speed, hand grip strength, and SARC-F questionnaire scores.Results: The results showed that participants aged 71– 80 years who practiced yoga for more than a year had significantly higher IGF-1 levels (p=0.04). While improvements in gait speed, hand grip strength, and SARC-F scores were observed, these changes were not statistically significant, and no significant differences were found in telomere length.Conclusion: Yoga in older adults was associated with higher IGF-1 levels and potential improvements in upper and lower extremity strength, though these findings were not statistically significant and did not influence telomere length. Yoga practice shows potential as an emerging adjuvant option but can not be applied as a single strategy for sarcopenia prevention in older adults.Keywords: aging, frailty, quality of life, yoga